CARS INPUT PROCESS EFFECT ON PROPOSAL OF LIGHT CONTROLLED INTERSECTION CONTROL PLAN - SIMULATION STUDY (Perner's Contacts, 2011)
The paper deals with an experimental evaluation of the impact of cars input  process on proposal of light controlled intersection control plan. The problem is  investigated on an imaginary simplified crossroad by using an simulation approach  by means of software Witness.
Keywords: Signalized Intersection; Control Plan; Input process; Erlang distribution; Simulation; witness